Exploring the Determinants of Entrepreneurial Intention of University Students - Shrestha, Purna Man (Journal of Entrepreneurship & Management Studies, 2024)
An entrepreneur's role is very crucial for achieving economic growth by creating employment opportunities in the country. Entrepreneurial activities are the outcome of the entrepreneurial intentions of individuals, which depend on several factors. For identification of the dynamics affecting of the factors affecting the entrepreneurial intention, this paper used the component of EET along with EE. For this purpose, a structured questionnaire survey was conducted using a sample of 384 students studying at the Graduate School of Management, Mid-West University, Nepal. This paper finds the influencing positive role of components of EET and EE in determining the EI of students. Thus, it is concluded that dimensions of EET and EE should be considered positively for developing the EI of university students. Thus, Nepalese universities should provide effective entrepreneurial education to their students to stimulate them as entrepreneurs.